Conservation on contested lands: the case of Namibia’s communal conservancies - Gargallo, E. (Journal of Contemporary African Studies, 2015)
Community Conservation initiatives have become widespread in several Southern African countries and have also been increasingly involved in disputes over land claims, control of resources and territorial authority. The aim of this paper is to analyse how Communal Conservancies in Namibia are being used by rural communities as tools for gaining or securing access to and control of communal land in a moment when it is perceived as increasingly scarce. Peasants, Traditional Authorities, the State and conservationists all try to influence the use that will be given to contested lands. The paper will focus on two cases: King Nehale Conservancy, a heavily populated mixed agricultural land in North-Central Namibia (Owamboland) and Nyae Nyae Conservancy, a semi-arid land inhabited by a historically marginalised population, the Ju/’hoan San. In both cases Conservancies contribute to an increased control by communities over their land, but also imply the reinforcement of the presence of the State and private capital in communal areas, and become part of the internal struggles among sections of the communities themselves.